Therapeutic management of hyperlipoproteinemia (a) - Constantine E Kosmas; Andreas Sourlas; Gordon Mallarkey; Delia Silverio; Domingo Y Ynoa; Peter D Montan; Eliscer Guzman; Mario J Garcia (BioExcel Publishing Ltd, 2019)
Cardiovascular disease (CVD) has consistently been the leading cause of death worldwide. Several clinical and epidemiological studies have demonstrated that an elevated plasma concentration of lipoprotein (a) [Lp(a)] is a causative and independent major risk factor for the development of CVD, as well as calcific aortic valve stenosis. Thus, the therapeutic management of hyperlipoproteinemia (a) has received much attention, as significant reductions in Lp(a) levels may, potentially, favorably affect cardiovascular risk. Aspirin, niacin, estrogens, and statins, which act on different molecular pathways, may be prescribed to patients with mild or modest elevations of Lp(a) levels. Other therapeutic interventions, such as proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors, Lp(a) apheresis, and the novel antisense oligonucleotides APO(a)-Rx and APO(a)-LRx, which are being evaluated in ongoing clinical trials, have provided some promising results and can potentially be used in severe cases of hyperlipoproteinemia (a). This review aims to present and discuss the current clinical and scientific data pertaining to the therapeutic options for the management of hyperlipoproteinemia (a).